Straw-boards from Rajasthan Raw Material - Guha, S. R. D.; Madas, R. N.; Kumar, Krishan (Indian Forester, 1979)
Stem of Bajra (Pennistum typhoides), Bui (Kochia indica) and Khimp (Leptadenia pyrotechnica) were pulped by lime process for the production of straw boards on the laboratory scale. The strength properties of board sheets from all the raw materials meet the strength properties recommended by I.S.I.